Behavioral and anatomical characterization of the bilateral sciatic nerve chronic constriction (bCCI) injury: correlation of anatomic changes and responses to cold stimuli - Kline Robert H; Chatterjee Koel; Datta Sukdeb; Wiley Ronald G (SAGE Publishing, 2010)
Abstract Background Unilateral constrictive sciatic nerve injury (uCCI) is a common neuropathic pain model. However, the bilateral constrictive injury (bCCI) model is less well studied, and shows unique characteristics. In the present study, we sought to correlate effects of bCCI on nocifensive responses to cold and mechanical stimuli with selected dorsal horn anatomic markers. bCCI or sham ligation of both rat sciatic nerves were followed up to 90 days of behavioural testing. Additional rats sacrificed at 15, 30 and 90 days were used for anatomic analyses. Behavioural tests included hindpaw withdrawal responses to topical acetone, cold plate testing, an operant thermal preference task and hindpaw withdrawal thresholds to mechanical probing. Results All nocifensive responses to cold increased and remained enhanced for >45 days. Mechanical withdrawal thresholds decreased for 25 days only. Densitometric analyses of immunoperoxidase staining in the superficial dorsal horn at L4-5 revealed decreased cholecystokinin (CCK) staining at all times after bCCI, decreased mu opiate receptor (MOR) staining, maximal at 15 days, increased neuropeptide Y (NPY) staining only at days 15 and 30, and increased neurokinin-1 receptor (NK-1R) staining at all time points, maximal at 15 days. Correlation analyses at 45 days post-bCCI, were significant for individual rat nocifensive responses in each cold test and CCK and NK-1R, but not for MOR or NPY. Conclusions These results confirm the usefulness of cold testing in bCCI rats, a new approach using CCI to model neuropathic pain, and suggest a potential value of studying the roles of dorsal horn CCK and substance P in chronic neuropathic pain. Compared to human subjects with neuropathic pain, responses to cold stimuli in rats with bCCI may be a useful model of neuropathic pain.